2022
DOI: 10.3389/feduc.2022.891534
|View full text |Cite
|
Sign up to set email alerts
|

Academic Writing Challenges and Supports: Perspectives of International Doctoral Students and Their Supervisors

Abstract: IntroductionAcademic writing is a core element of a successful graduate program, especially at the doctoral level. Graduate students are expected to write in a scholarly manner for their thesis and scholarly publications. However, in some cases, limited or no specific training on academic writing is provided to them to do this effectively. As a result, many graduate students, especially those having English as an Additional Language (EAL), face significant challenges in scholarly writing. Further, faculty supe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1
7

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
1
10
1
7
Order By: Relevance
“…while most of the respondents (54.2%) reported it was a challenge only to an extent, with a quarter (25.1%) solidly agreeing that proficiency affected their academic writing. These responses are consistent with Sidman-Taveau and Karathanos-Aguilar (2015), Flowerdew (2019), andGupta et al 's (2022) findings that academic writing forms an additional area of burden for additional language students. This is bearing in mind the well documented challenges with academic writing faced even by students for whom English is a native language (Tang, 2012;AlMarwani, 2020), who generally encounter challenges with generic academic writing competency.…”
Section: Factor Percentagesupporting
confidence: 89%
See 2 more Smart Citations
“…while most of the respondents (54.2%) reported it was a challenge only to an extent, with a quarter (25.1%) solidly agreeing that proficiency affected their academic writing. These responses are consistent with Sidman-Taveau and Karathanos-Aguilar (2015), Flowerdew (2019), andGupta et al 's (2022) findings that academic writing forms an additional area of burden for additional language students. This is bearing in mind the well documented challenges with academic writing faced even by students for whom English is a native language (Tang, 2012;AlMarwani, 2020), who generally encounter challenges with generic academic writing competency.…”
Section: Factor Percentagesupporting
confidence: 89%
“…This further shows the extent to which the SLH programs are evolving demographically, therefore raising implications for necessary intentional steps by the SLH department at the University to provide support to this group of students based on the rurality factor. This support is necessary from the students' very point of entry into the programs and throughout their studies as exemplified by Gupta et al (2022) who suggested support strategies related to academic writing. These support strategies entailed academic staff members providing training to EAL students in terms of appropriate discipline-specific writing via seminars and workshops from the first point of entry into the faculty.…”
Section: Participant Description and Demographicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors discuss the creation of accessible online learning environments (O'Flaherty and Costabile, 2020), the impact of research writing tutors during revision (Cotos, Huffman and Link, 2020), problem-based learning on enhancing problem-solving and scientific writing skills (Sari et al, 2021), and how the use of learning media and pedagogical approaches can enhance the teaching of scientific writing for doctoral students (Leberecht, 2021). Additionally, other scholars explore the various challenges and supports associated with academic writing (Gupta et al, 2022); Gupta et al (2022) propose a virtual writing workshop, while Bottomley and Bourgeois (2022) suggest a similar method. Hands and Tucker (2022) advocate for writing pedagogy.…”
Section: Introductionmentioning
confidence: 99%
“…Unfortunately, numerous students come into programs with inadequate writing skills and lack experience with disciplinary writing patterns (Gupta et al, 2022;Maher et al, 2014). Although students show weaknesses in their writing skills, we must also recognize the expectations for quality academic writing lack transparency (Inouye & McAlpine, 2019;Zhang & Hyland, 2021) leaving students with only vague targets to guide their writing development.…”
Section: Introductionmentioning
confidence: 99%